Malignant melanoma: A rare case report - Mallika Kishore; Sunil R Panat; Abhinav Kishore; Abhijeet Alok (Wolters Kluwer Medknow Publications, 2016)
Malignant melanoma in the oral cavity accounts for only 0.2-8% of all malignant melanomas and it has a much poorer prognosis than its counterpart on the skin. Due to the greater tendency toward metastasis, oral melanoma is considered quite aggressive. Early diagnosis and treatment are essential for a better prognosis regarding melanomas and a reduced risk of mortality from them. To date, very few cases have been reported, according to the data we have collected. Literature search shows that oral malignant melanoma was often implicated on the maxillary gingiva compared to the mandibular gingiva. In contrast, we describe a case of malignant melanoma on the mandibular gingiva in this report. This is a rare presentation for the condition which is detailed in this case report of malignant melanoma in a 57-year-old male who presented with painless, pigmented swelling on the mandibular gingiva.